Evaluasi Penerapan Moodle Dalam Pembelajaran Kejuruan Menggunakan Gibb's Reflective Learning Cycle - Lukman Rian Affandi; Muji Lestari (Journal of Informatics and Vocational Education, 2022)
Good interaction between educators and learners can encourage the achievement of learning objectives. However, if the interaction goes well, the result will be the opposite. Moreover, the learning process needs to encourage students to think critically. However, it will instead become a burden in the learning process so that there is no collaboration between students during the learning process. This study aims to understand the perceptions of teachers and students towards the application of the Moodle Learning Management System (LMS) to improve learning outcomes that are still low using several types of learning media. This research uses a qualitative approach with Gibb's Reflective Learning Cycle technique to obtain the perceptions of educators and students. This research was conducted because, in the learning process, many still need to learn to use technology appropriately. The media used is less innovative and limited, so learning has yet to be created that encourages students to think critically and comprehensively. Unlike moodle research in general, this research is used to evaluate two sides of using technology, especially moodle, in helping the learning process, namely on the side of educators and students.